Pesantren dan Transmisi Keilmuan Islam Melayu-Nusantara; Literasi, Teks, Kitab dan Sanad Keilmuan - Ulfatun Hasanah (Institut Ilmu Keislaman Annuqayah, 2015)
A Gus Dur’s terminological reference ‘Sub-Culture’ to Pesantren indicates that this institution is closely related to society. It is because of a fact that pesantren has been developed from, by, and for society. From its initial function as literate society, a center for reduction of social illiteracy, until as cultural literacy, a castle of socio-cultural defense, this institution has became an archipelago-based-islamic institution and a center of Muslim civilization in its intelectual roots of tradition, including al-turats, genealogical lineage of science, etc. At-turats (kitab kuning) serves as a medium of networking ulama’ in the spreading of islamic knowledge. The tradition of at-turats and the moral relationship between teachers and students has became social ground of pesantren building. This relationship has been embedded into the tradition of at-turats in order to maintain the genealogical linkage of science transmission (sanad). Instead of contradictionary, these elements are complementary for maintaining Pesantren as ‘sub-culture’.